Reinforced and superinsulating silica aerogel through in situ cross-linking with silane terminated prepolymers. (1st April 2018) - Iswar, Subramaniam; Snellings, Geert M.B.F.; Zhao, Shanyu; Erni, Rolf; Bahk, Yeon Kyoung; Wang, Jing; Lattuada, Marco; Koebel, Matthias M.; Malfait, Wim J.
Abstract: Silica aerogels have only half the thermal conductivity of conventional insulation, but their application potential is limited by the poor mechanical properties. The fragility arises from the thin necks between the silica nanoparticle building blocks. Here, we produce strong silica aerogels through co-gelation of the polyethoxydisiloxane precursor with a variety of silane terminated prepolymers that reinforce the inter-particle necks, followed by hydrophobization and supercritical CO2 drying. All prepolymers enabled the synthesis of aerogels with excellent thermal and mechanical properties, but the shortest prepolymer (∼2–3 nm long) yielded the best results. The hybrid aerogels can sustain uniaxial compression without brittle rupture to at least 80% strain for all prepolymer concentrations (5–50 wt%), leading to a final strength of up to 21 MPa, an E modulus up to 3.4 MPa, and an up to 400 times lower dust release rate. In contrast to classical reinforcement strategies, the mechanical improvement does not come with a penalty in thermal conductivity, which remains between 14 and 17 mW m −1 K −1 . The hybrid aerogels are a unique class of superinsulating materials with superior thermal and mechanical properties and a scalable production process. Graphical abstract: Image 1